Unconstrained Text Detection in Manga: a New Dataset and Baseline [Data set] - Matuk Herrera, Rosana (2021)
Fil: Matuk Herrera, Rosana. Departamento de Ciencias Básicas. Universidad Nacional de Luján; Argentina